Legal Certainty of the Meaning of the Parties' Agreement on the Authorized Capital of a Limited Liability Company - Helex Wirawan; Fauzie Yusuf Hasibuan; Atma Suganda (Asian Journal of Social and Humanities, 2024)
The impact of changing the amount of PT capital to an agreement between the parties has led to a lack of legal certainty for the involved parties. A significant legal conflict exists between Article 32 paragraph (1) of Law Number 40 of 2007 concerning Limited Liability Companies and Article 109 paragraph (1) of Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation. The changes allow the amount of PT capital to be determined based on the agreement of the company's founders, leading to ambiguity in legal certainty. This research aims to examine and analyze the legal consequences of these regulations on the basic capital requirements for Limited Liability Companies in Indonesia, and to assess the legal certainty surrounding the agreement between parties regarding PT capital. The research employs a normative juridical method, utilizing statutory, comparative, and conceptual approaches. The analysis is grounded in the Theory of Legal Certainty (Grand Theory), Development Law Theory (Middle Range Theory), and the Theory of Good Corporate Governance (Applied Theory). The research found that changes in the regulation of basic capital, following the enactment of Law No. 6 of 2023, have contributed to legal uncertainty. This study aims to provide legal clarity on the consequences of these regulatory changes and their impact on corporate governance and legal compliance in Indonesia.